Der Parasitoidenkomplex der Apfelblattminiermotte (Stigmella malella Stt.) im Havelländischen Obstbaugebiet (Lepidoptera, Nepticulidae). - Mey, Wolfram (Contributions to Entomology = Beiträge zur Entomologie, 1989)
The Parasitoid-complex of the apple leaf-miner Stigmella malella Stt. contains 13 species. They belong mostly to the family Eulophidae (Chalcidoidea). The life cycle of the common species is presented including additional notes to ecological traits. The polyphagous Cirrospilus vittatus Walker and Chrysonotomyia chlorogaster Erdös are the prevailing parasitoids of the host larvae. Chrysocharis prodice Walker emerges from the cocoons. He goes around as an oligophagous species attacking only members of the large genus Stigmella and is regarded as the most important natural enemy of St. malella. In orchards without any plant protection measures the parasitization rates often reach high levels. At this unaffected sites the parasitoid-complex is acting as a density-dependent mortality factor working best at low host abundances. In the intensively sprayed orchards the percent parasitism of the leaf-miner populations shows low values and has no practical importance. The high toxicity and persistence of the broad spectrum insecticides and acaricides usually applied in the district prevent a sufficient parasitization. This is supposed to be one of the causes underlying the development of St. malella to a secondary pest species. The possible control of the leaf-miner by its parasitoid-complex depends largely on the substitution of the hitherto used pesticides against tortricid moths by selective agents.